Quantitative Analysis of the Impact of Floods in Bolivia - Ishizawa, Oscar A.; Miranda, Juan José; Jiménez, Luis Felipe; Villamil, Andrea; Lv, Xijie; Jardillier, Remy Paul Jean; de Haro López, Itzel (World Bank, Washington, DC, 2017)
Bolivia’s primary natural hazards - such as droughts, frost, severe rains, and hailstorms - are largely hydrometeorological in nature, and include phenomena derived from these, such as floods and landslides. Given their frequency and the proportion of the population exposed to them, floods cause significant economic losses primarily affecting infrastructure, agricultural, and livestock production. Given this context, disaster risk management has been a priority in the agenda of the Government of Bolivia, which has achieved significant progress in establishing a regulatory and institutional framework for this purpose. This study analyzes various indexes commonly used in economic literature to represent flood impacts. The results show that different indexes are consistent across the different characterizations, and point to a significant negative effect of excessive precipitation, intense rainfall, and river overflow, on both per capita income and household poverty. The study is divided into four sections. The first section describes the three indexes used in the study, the information used to calibrate them, and how their values are calculated. The second section describes the methodology used to assess floods imparts on household income and poverty. The third section describes the results for different variants of the indexes and includes a comparison of the predictions of each in different scenarios. The last section shows the main conclusions of the study.